Host-pathogen interactions between the human innate immune system and Candida albicans—understanding and modeling defense and evasion strategies - Dühring, Sybille; Germerodt, Sebastian; Skerka, Christine; Zipfel, Peter F.; Dandekar, Thomas; Schuster, Stefan (Frontiers in Microbiology, 2015)
The diploid, polymorphic yeast Candida albicans is one of the most important human pathogenic fungi. C. albicans can grow, proliferate and coexist as a commensal on or within the human host for a long time. Alterations in the host environment, however, can render C. albicans virulent. In this review, we describe the immunological cross-talk between C. albicans and the human innate immune system. We give an overview in form of pairs of human defense strategies including immunological mechanisms as well as general stressors such as nutrient limitation, pH, fever etc. and the corresponding fungal response and evasion mechanisms. Furthermore Computational Systems Biology approaches to model and investigate these complex interaction are highlighted with a special focus on game-theoretical methods and agent-based models. An outlook on interesting questions to be tackled by Systems Biology regarding entangled defense and evasion mechanisms is given.